Tools to Incorporate Biomimetic into Product Design- A Review - Maidin, S.; Romlee, W.F.A.; Mohamed, A.S.; Ung, J.W.H.; Akmal, S. (Journal of Advanced Manufacturing Technology (JAMT), 2018)
This paper reviewed available biomimetic tools which are being utilized to enhance and aid the design of products.  So far, tools that have been used to gain insight of biomimetic products include DANE databases and IDEA-INSPIRE, Natural Language analysis tool and Asknature.org website. This review focused on the representations, characteristics and biomimetic information retrieval process of each search tools studied by previous researchers. Finally, the conclusions and important summaries were presented accordingly in the form of a table. Based on the findings, there are still problems and challenges regarding the applications of each tool in the bio-inspired design process. Some suggestions have been made to further improve the conditions.